2018
DOI: 10.19173/irrodl.v19i4.3489
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Knowledge: Pre-Assessment and Post-Assessment of MOOC Participants From an Energy and Sustainability Project

Abstract: Understanding factors promoting or preventing participants’ completion of a massive open online course (MOOC) is an important research topic, as attrition rates remain high for this environment.  Motivation and digital skills have been identified as aspects promoting student engagement in a MOOC, and they are considered necessary for success.  However, evaluation of these factors has often relied on tools for which the psychometric properties have not been explored; this suggests that researchers may be workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
0
21
0
2
Order By: Relevance
“…In this direction, Hew and Cheung (2014) stated that learning is one of the reasons for individuals to participate in MOOCs. Similarly, Vázquez, Ramirez-Montoya, and Gónzalez (2018) expressed that completers in MOOCs have more motivation at the beginning of the course. Therefore, determining the initial motivations of participants can help to prepare remedial interventions.…”
Section: The Factors Affecting Online Course Completion With Respect mentioning
confidence: 99%
“…In this direction, Hew and Cheung (2014) stated that learning is one of the reasons for individuals to participate in MOOCs. Similarly, Vázquez, Ramirez-Montoya, and Gónzalez (2018) expressed that completers in MOOCs have more motivation at the beginning of the course. Therefore, determining the initial motivations of participants can help to prepare remedial interventions.…”
Section: The Factors Affecting Online Course Completion With Respect mentioning
confidence: 99%
“…In response to the general objective of this research, it was found that personal factors [3,4], family factors [8][9][10], social factors [14], instructional design factors [17,18] and labor factors [29] influence both the decision to take a MOOC (expectation-value) and, to a certain extent, engagement in the training program-measured by completion rates-as noted in the review of the state of the art. However, not all factors do so in the same way.…”
Section: Discussionmentioning
confidence: 96%
“…Familiar factors also have a relation to the commitment of MOOC participants. Several studies have developed instruments that consider the background and demographic data as substantial [8] and literature reviews that highlight the importance of building academic commitment and self-regulation to be effective [9,10]. Self-efficacy takes into account student characteristics to understand why some students do not complete these courses [11], where the theory of self-determination touches on issues and sections such as participants' autonomy, competence, and affinity, and based on this, studies and analyzes the background of MOOC participants [12].…”
Section: Introductionmentioning
confidence: 99%
“…Engagement is defined as "the behavioral intensity and emotional quality of a person's active involvement during a task" (Reeve, Jang, Carrell, Jeon, & Barch, 2004, 147). Engagement in traditional classroom settings are usually associated with improved course satisfaction, improved motivation, more participation in academic activities, and more success levels success levels (de Barba, Kennedy & Ainley 2016;Valdivia, Ramírez-Montoya, & Valenzuela, 2018).…”
Section: Engagement In Learningmentioning
confidence: 99%